Tight interaction of eEF2 in the presence of Stm1 on ribosome. (23rd October 2017) - Hayashi, Hikari; Nagai, Riku; Abe, Taisho; Wada, Miki; Ito, Koichi; Takeuchi-Tomita, Nono
Abstract: The stress-related protein Stm1 interacts with ribosomes, and is implicated in repressing translation. Stm1 was previously studied both in vivo and in vitro by cell-free translation systems using crude yeast lysates, but its precise functional mechanism remains obscure. Using an in vitro reconstituted translation system, we now show that Stm1 severely inhibits translation through its N-terminal region, aa 1 to 107, and this inhibition is antagonized by eEF3. We found that Stm1 stabilizes eEF2 on the 80 S ribosome in the GTP-bound form, independently of eEF2's diphthamide modification, a conserved post-translational modification at the tip of domain IV. Systematic analyses of N- or C-terminal truncated mutants revealed that the core region of Stm1, aa 47 to 143, is crucial for its ribosome binding and eEF2 stabilization. Stm1 does not inhibit the 80 S-dependent GTPase activity of eEF2, at least during the first round of GTP-hydrolysis. The mechanism and the role of the stable association of eEF2 with the ribosome in the presence of Stm1 are discussed in relation to the translation repression by Stm1.